1986
DOI: 10.1111/j.1651-2227.1986.tb10222.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Size and Function of the Remnant Kidney in Patients Nephrectomized in Childhood for Wilms’Tumor and Hydronephrosis

Abstract: To obtain more information about the natural history of compensatory renal hypertrophy beginning in childhood we traced those who were nephrectomized in childhood for Wilm's tumor (W) and hydronephrosis (Hn) between 1950 and 1978 at one department of surgery in Stockholm. All W patients had received treatment that suppresses cellular division. None of the patients were in renal failure or treated with antihypertensive drugs. All the patients in the follow-up study (22 W, 15 Hn) had a normal contralateral kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 26 publications
(2 reference statements)
1
18
0
Order By: Relevance
“…[23][24][25] Despite these studies, the long-term outlook for developing hypertension, proteinuria, and renal failure still remains somewhat controversial. Studies that have evaluated children who have had nephrectomy 21,26,27 or adults that served as a kidney donor 28,29 have found little or no difference in renal function and/or injury compared with control subjects. However, several recent studies have found kidney donors are at an increased risk (up to 8-fold) to develop renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Despite these studies, the long-term outlook for developing hypertension, proteinuria, and renal failure still remains somewhat controversial. Studies that have evaluated children who have had nephrectomy 21,26,27 or adults that served as a kidney donor 28,29 have found little or no difference in renal function and/or injury compared with control subjects. However, several recent studies have found kidney donors are at an increased risk (up to 8-fold) to develop renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Renal size (measured by ultrasound) was evaluated using the formula: length6width6(longitudinal+transverse depth)/ 260.523 (Wikstad et al, 1986).…”
Section: Renal Investigationsmentioning
confidence: 99%
“…Reported effects after treatment for Wilms' tumour have included reduction in glomerular filtration rate (GFR) (Walker et al, 1982;Robitalle et al, 1985;Levitt et al, 1992), microalbuminuria (Levitt et al, 1992;di Tullio et al, 1996) (rarely resulting in hyperfiltration induced glomerulosclerosis and subsequent renal failure), failure of compensatory hypertrophy of the remaining kidney (Wikstad et al, 1986;Makipernaa et al, 1991;Levitt et al, 1992) and hypertension (Levitt et al, 1992).…”
mentioning
confidence: 99%
“…Several studies have shown that there is compensatory renal growth in patients treated for Wilms' tumour with multimodality therapy (Walker et al, 1982;Luttenegger et al, 1975;Dinkel et al, 1988), but less than in children who have nephrectomy for non-malignant conditions. There are few reports of both renal growth and function in long-term survivors of Wilms' tumour and the number of patients in these studies is small (Wikstad et al, 1986;Makipernaa et al, 1991).…”
mentioning
confidence: 99%